Assessing Economic and Infrastructure Constraints on Electric Vehicle Purchase Decisions: A Demographic-Moderated Analysis in Emerging Markets - Alzoubi, Haitham M.; Alshurideh, Muhammad Turki; Al-Gharaibeh, Shehadeh Mofleh; Al-Shyaab, Khaled Omar Mohammad; Al Kurdi, Barween; Al-Sulaiti, Ibrahim; Ahmed, Gouher; Bataineh, Abdallah Q.; Alquqa, Enass Khalil (International Journal of Energy Economics and Policy, 2025)
Electric vehicle (EV) adoption is gaining global attention; however, economic and infrastructure barriers remain critical challenges in emerging markets. This study examines the impact of economic constraints (high purchase costs, maintenance expenses, and spare parts availability) and infrastructure limitations (Charging Infrastructure Availability, charging time, and spare parts supply chain inefficiencies) on EV purchase decisions in Jordan. The study further investigates the moderating role of demographics (age, gender, and education level) in shaping consumer responses to these constraints. The research employed Structural Equation Modeling (SEM) as a quantitative method to examine data obtained from Jordanian EV consumer prospects. The adoption of EVs depends heavily on economic and infrastructure factors where infrastructure play a dominant role. The demographic characteristics determine how consumers handle obstacles that prevent them from adopting electric vehicles. The research enhances theoretical EV adoption frameworks through economic and infrastructure analysis combined with demographic variables which improves our understanding of purchase choices in developing markets. The implementation of policy needs to concentrate on building charging infrastructure along with supply chain optimization and targeted incentives for different groups of people. The research provides strategic guidance for policy makers as well as businesses and industry stakeholders to accelerate sustainable transportation adoption in emerging market settings.